2020
DOI: 10.1590/0103-8478cr20191020
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac structural and functional findings in Persian cats with autosomal dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) has been related to left ventricular structural and functional abnormalities in human patients. The present study aimed to evaluate the cardiac structural and functional findings in Persian cats with ADPKD. Client-owned ADPKD (n=12) and non-ADPKD (n=12) Persian cats were enrolled in this study. The animals underwent echo- and electrocardiographic (ECG) examinations, and non-invasive measurements of systolic blood pressure (SBP) were obtained. Both groups wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Nururrozi et al (2021) reported clinical signs of PKD in Persian cats include subnormal body temperature (36.3 ºC), slow skin turgor, pale mucous membranes, capillary refill time of more than 2 seconds, dehydration (8%), left submandibular lymphadenitis, rhonchi respiratory sound, halitosis, and hypersalivation. Guerra et al (2020) also reported the symptoms of PKD as fatigue, cough, emaciation, dyspnea, cyanosis, exercise intolerance, syncope or pre-syncope, convulsion, and ascites. However, not all PKD cats exhibit clinical symptoms indicative of renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Nururrozi et al (2021) reported clinical signs of PKD in Persian cats include subnormal body temperature (36.3 ºC), slow skin turgor, pale mucous membranes, capillary refill time of more than 2 seconds, dehydration (8%), left submandibular lymphadenitis, rhonchi respiratory sound, halitosis, and hypersalivation. Guerra et al (2020) also reported the symptoms of PKD as fatigue, cough, emaciation, dyspnea, cyanosis, exercise intolerance, syncope or pre-syncope, convulsion, and ascites. However, not all PKD cats exhibit clinical symptoms indicative of renal disease.…”
Section: Introductionmentioning
confidence: 99%